Spinal Hydatidosis Relapse: A Case Report. (20th July 2014) - Fiori, Roberto; Coco, Irene; Nezzo, Marco; Kabunda, Gisèle; Umana, Giuseppe Emmanuele; Fraioli, Mario Francesco; Simonetti, Giovanni
Abstract : Human cystic echinococcosis (CE) is a zoonosis caused by the larval stage of the Echinococcus granulosus and the most common sites affected are the liver and lung in approximately 80–90% of cases. The hydatid bone represents the 0.5–2.5% of all cases and localization cord is present about 50% of the time. This benign and commonly asymptomatic disease may simulate an aggressive malignancy because of osseous destruction and aggressive extension. We report a case of a 42-year-old male patient, presented with an unusual spinal hydatidosis relapse, related to anthelmintic drug therapy withdrawal after 10-year treatment. The man had previous excision of chest and hepatic hydatid cysts (resp., 10 and 3 years ago) and after primary mediastinal and spinal involvement (3 years ago) he was lost to follow-up and discontinued drug therapy. The patient underwent surgery and the postoperative histopathology confirmed the diagnosis. The patient recovered with no complications. Despite significant progress in diagnostic imaging, pharmacological and surgical therapy, spinal CE remains associated with high morbidity.